The problem of job obsolescence and spatial creation of indigenous industries and their economic determinants in Wasit Governorate - Minshid, Ahlam Noori (Al-Adab Journal, 2022)
The study of functional aging and spatial creation of indigenous industries and their economic determinants from industrial geographic studies that depend on the applied and statistical approach, helps in giving numerical and quantitative indicators of the natural, human and technological changes of the original industries and how the attraction, polarization, spatial differences and the environment can be used in the production of new products by alternative industries. Which was developed according to the spatial elements that show the importance of the existence of new industrial sites, and thus activating the industrial movement in the regions and cities of the governorate, so we find that studying such topics requires a large information cooperation between the competent authorities to obtain development and industrial data, as well as economic data that enables The researcher was able to reach the required levels of sustainability, job aging ratios and spatial creation of original industries through the application of statistical programs, including the statistical program spss-v17, and the economic industrial measurement software EVIEWS 10.5, to extract the digital results, which gave importance to the data extracted from the analysis of the tables mentioned below, as well. Helped use Quantitative Excel programs, and the v14-minitab program, to reach accurate industrial indicators that enabled the research to come up with immediate and future digital outputs of how to determine the economic determinants affecting the original industries and create other developmental ones for the industry, making it more effective to achieve high economic development rates. The research focused on topics related to The spatial distribution of the original industries and its impact on the aging and creation and the spatial relative distribution of the population and workers in various industries, as it came to the districts of Kalati (588221,243076,286288,156370,142614,52526) respectively, as well as the economically active population in Wasit Governorate by gender for the period (2018-2019). 2020), showing the indicators of the industrial structure of the original industries and the impact of geographical and industrial determinants and the obstacles affecting the functional aging and spatial creation of the original industries in Wasit Governorate, and the statistical analysis of the ratios of quantitative concentration coefficients in the districts of food industries came (1,2, 1,1, 0,1 (0,3, 1,3, 0,4%), respectively, the size of the variance, the structural difference, and the redistribution coefficients of the newly created volumetric composition, as well as the density ratios, the strength of the fabrication and the The least and most innovations took place according to the original industries, as their percentages were recorded (0.68,0.40,0,57,0,31,0,20,0,34,0,39,0.27,0,55, 0,56) respectively. Its reflection on the proportion of the industrial interconnectedness of the original industries using the v17 spss and v14-minitab program, and how to benefit from the redundant and newly developed industries to improve the economic development measurement in Wasit governorate for the year 2020, and the percentages of the indicators of proportionality, complementarity, dependability and efficiency of the original and subsidiary industries created in the research area came to help in Extracting results based on EVIEWS 10.5 for sustainable measurement and v14-minitab in the governorate from 2020 to 2030